PUBLIC RELATIONS STRATEGY IN BUILDING PERSONAL BRANDING OF VISUAL ARTISTS - Rina Sovianti; Sari Enda Nursyamsi; Nazaruddin Siregar (Jurnal Ekonomi, 2023)
Personal branding is a way to describe yourself briefly and is easy to remember. With Muklay's personal branding in the arts as a visual artist, Muklay needs a public relations strategy to build personal branding to make it easier to get closer to the public. Then this research will explain how the public relations strategy in terms of PENCILS strategy to build personal branding. This research uses a qualitative method with a narrative approach. Data collection techniques through interviews, observation, and documentation. In-depth interviews were conducted with key informants namely Muklay and additional informants namely from Gardu House, Detik.com, and one of Muklay's clients. The results of this research indicate that Muklay has built personal branding as a visual artist through publications, events, news, dealing with the community, dealing with the media, lobbying and negotiating, and participating in social activities. The PENCILS strategy proved to be successful with the breadth of Muklay's relations with many people who had different backgrounds, not just in the arts